2000
DOI: 10.1103/physrevb.62.11089
|View full text |Cite
|
Sign up to set email alerts
|

Density,sp3fraction, and cross-sectional structure of amorphous carbon films determined by x-ray reflectivity and electron energy-loss spectroscopy

Abstract: Grazing-angle x-ray reflectivity ͑XRR͒ is described as an efficient, nondestructive, parameter-free means to measure the mass density of various types of amorphous carbon films down to the nanometer thickness range. It is shown how XRR can also detect layering if it is present in the films, in which case the reflectivity profile must be modeled to derive the density. The mass density can also be derived from the valence electron density via the plasmon energy, which is measured by electron energy-loss spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
317
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 531 publications
(349 citation statements)
references
References 72 publications
30
317
1
1
Order By: Relevance
“…The EELS data revealed that all films had a high sp 3 content, sp 3 /(sp 2 +sp 3 ), see fraction correlates with the plasmon-inferred densities and, with the exception of sample 4 , this trend follows that proposed by Ferrari et al [9] (albeit using m* = 0.87 m e ).…”
Section: Lbnl-59023supporting
confidence: 62%
See 2 more Smart Citations
“…The EELS data revealed that all films had a high sp 3 content, sp 3 /(sp 2 +sp 3 ), see fraction correlates with the plasmon-inferred densities and, with the exception of sample 4 , this trend follows that proposed by Ferrari et al [9] (albeit using m* = 0.87 m e ).…”
Section: Lbnl-59023supporting
confidence: 62%
“…correlation between the plasmon-inferred density and the sp 3 content [9]. Experimental investigations [10] and theoretical considerations of ta-C [9] have shown that it is appropriate to use prescribe an effective mass m* ≅ 0.9 m e for the valence electrons when calculating the specimen density from the plasmon peak position, where m e is the rest mass of the electron.…”
Section: Lbnl-59023mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we addressed this issue by conceiving and implementing a strategy [18] which entailed increase of the electron temperature in high electron density discharge (such as HiPIMS) by using higher ionization potential buffer gas, Ne, instead of Ar. The result was a substantial increase in the ionized fraction of C which facilitated an increase in mass densities of films to levels which are close to those obtained by CVA and PLD [8,10].…”
Section: Introductionmentioning
confidence: 60%
“…Bonding configuration and hydrogen content can be, in turn, tailored by controlling the energy and flux of the depositing species [5,6]. An efficient way to achieve this is by using ionized deposition fluxes which can be generated by high plasma density discharges, such as cathodic vacuum arc (CVA) [8,9], pulsed laser deposition (PLD) [10,11], inductively coupled plasma (ICP) [12] and electron cyclotron resonance (ECR) [13] based plasma enhanced chemical vapor deposition (PECVD). Synthesis of a-C using magnetron sputtering-based discharges may be more industrially relevant owing to their conceptual simplicity and scalability.…”
Section: Introductionmentioning
confidence: 99%